Pembuatan Antarmuka Website Desa Jambuwuluk Menggunakan Metode User Centered Design - Sambo, Denis Irwanto; Nugraha, Kristian Adi; Delima, Rosa (Jurnal Terapan Teknologi Informasi, 2023)
The information technology used in Jambuluwuk Village Office consists of computer devices that utilize a system provided by the village government to assist in the administrative services of Jambuluwuk Village. This system can be accessed easily by the community and village staff anytime and anywhere through the village's website at https://jambuluwuk.online/, using an internet connection. Despite the positive aspects of the website, there are some issues identified on the Jambuluwuk Village website. One of the problems is the inconsistent display in one of the menus, namely the Village Government menu, which discusses the organizational structure of the village administration. The organizational structure is important information for the residents, particularly the Jambuluwuk Village staff. Currently, the Village Government menu only displays the names of the village staff without utilizing charts or structures. This makes it difficult for the village staff to understand the organizational structure as there is no information explaining the hierarchy or levels of each division in Jambuluwuk Village. During the design and implementation of the Jambuluwuk Village website, the researcher utilized the User-Centered Design (UCD) method. This was done because the researcher focused on user requirements, and the method was optimized to fulfill the needs and desires of end users. Subsequently, the researcher conducted testing using the System Usability Scale (SUS) method. The website of Jambuluwuk Village has two actors: the admin and the users (village residents). The website is built using PHP, the Laravel framework, XAMPP, and the MySQL database.